xamining the Challenges and Problems Faced by Tourism Social Entrepreneurs in restoring craftsmanship at Conflict ridden tourist Destinations - Singh, Ramjit; Singh Manhas, Parikshat; Malik, Immad; Nazki, Adil Amin (Turizam, 2024)
The aim of this study is to examine the problems and challenges faced by the tourism social entrepreneurs in Kashmir Valley of Jammu and Kashmir, India which has been witnessing the crisis due to political instability. The study seeks to understand the various patterns for the development of craftsmanship as well as the role of tourism social entrepreneurship in shaping the livelihoods of craftsmen. This research study is based on a quantitative approach that constituted two hundred fifty nine respondents by employing a random sampling method. The data was analyzed through SPSS.25.0. The findings of the investigation revealed that marketing; financial problems; infrastructural deficiency and erroneous planning are the major problems and challenges faced by tourism social entrepreneurs in Kashmir. Also, the outcomes of the study indicate that social entrepreneurship in the tourism industry may take on a variety of forms and with the right management and support they can provide a lucrative career for artisans. The results of the research study can be utilized by academicians, practitioners, and research scholars for the purpose of theory building and further improvements in the subject area.